Predictors of Postdeployment Functioning in Combat-Exposed U.S. Military Veterans. (July 2017) - Disner, Seth G.; Kramer, Mark D.; Nelson, Nathaniel W.; Lipinski, Alexandra J.; Christensen, Julia M.; Polusny, Melissa A.; Sponheim, Scott R.
Posttraumatic stress disorder (PTSD) and sequelae of mild traumatic brain injury (mTBI) are presumed to contribute to reintegration difficulties in combat-exposed veterans. Yet their relative impacts on postdeployment functioning are not well understood. The current study used structural equation modeling (SEM) to clarify the extent to which symptoms of internalizing disorders (e.g., depression, anxiety), mTBI symptoms, and cognitive performance are associated with functional impairment in 295 combat-exposed veterans. SEM results showed that internalizing symptoms most significantly predicted functional impairment ( r = 0.72). Blast mTBI and cognitive performance were associated with internalizing ( r = 0.24 and −0.25, respectively), but functional impairment was only modestly related to cognition ( r = −0.17) and unrelated to mTBI. These results indicate that internalizing symptoms are the strongest predictor of functioning in trauma-exposed veterans, exceeding the effects of mTBI and cognitive performance. This evidence supports prioritizing interventions that target internalizing psychopathology to improve functioning in cases of co-occurring PTSD and mTBI.